ANALISIS STRUKTUR PENDAPATAN DAN POLA PENGELUARAN RUMAH TANGGA NELAYAN JARING KANTONG (TRAMMEL NET) DI KECAMATAN ALUH-ALUH KABUPATEN BANJAR - Gazali, Akhmad; Sofia, Leila Ariyani; Agusliani, Erma (EnviroScienteae, 2023)
Fishermen's income is sometimes very fluctuating, especially during the famine season which is usually marked by a decrease in the number of catches. This results in price fluctuations that have an impact on decreasing fishermen's income. The aim of this research is to analyze the income structure and expenditure patterns of trammel net fishermen in Aluh-Aluh district, Banjar district. This research was conducted in Aluh-aluh District, Aluh-Aluh District, Banjar Regency, South Kalimantan. Realization of the study location was carried out deliberately because the population uses a lot of fishing gear net bag (Trammel Net). The research was conducted from April to December 2022. The method used in this research is a descriptive method which can be interpreted as a problem solving procedure investigated by describing/ describe the condition of the subject/object of research. Total household income of bag net fishermen in Aluh-Aluh District, Banjar Regency, South Kalimantan Province. Income from catches from fishermen who own boats is IDR 104,814,532/year and income from farming in the paddy fields is IDR 17,188,750/year. Income from the catch of boat labor fishermen is Rp. 17,616,000/year and income from farming in the paddy fields Rp. 5,500,000/year. The total expenditure of pocket fishermen in Aluh-Aluh District, Banjar Regency, South Kalimantan Province consists of the expenditure pattern of fishermen who own boats, namely food consumption (rice, fish, vegetables and milk) and the expenditure pattern of labor fishermen, namely food consumption (rice, fish, vegetables and milk).